Training on Quizizz as Interactive Learning Media and Assessment for Primary Teacher: Pelatihan Aplikasi Quizizz sebagai Media Pembelajaran Interaktif dan Asemen Bagi Pendidik Sekolah Dasar - Andika, Refiona; Erita, Yeni; Ningsih, Yarisda (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2024)
The learning process expected by Curriculum Merdeka is to pay attention to the differences in the cognitive level of each student, and teachers facilitate each of those differences with differentiated learning. In addition, the assessment also follows the change, that the assessment no longer has to be carried out only at the middle of the semester or the end of the semester. However, expected assessments are those that are also carried out before, process, and after learning. The purpose of this activity is to provide training to elementary school teachers to design differentiated learning. In addition, it also equips teachers to be proficient in using the Quizizz application as an interactive assessment media. This activity was carried out in six sessions which were divided into seminars and training. The results of the activity showed an increase in the knowledge of the teacher about differentiated learning. In addition, improvements were also seen in the skills of elementary school teachers in using the Quizizz application as an interactive assessment tool. This training can encourage teachers to use smart devices in teaching and learning activities, as a stimulus for students to learn fun, in accordance with technological developments.